The Influence of Value Added Capital Employed (VACA) and Structural Capital Value Added (STVA) on Return on Assets (ROA) at Indonesian Government Banks - Caroline Eka Putri Oktaviani; Ita Janah; Ario Purdianto (Indonesian Journal of Business Analytics, 2025)
In addition to being a supporting component, knowledge also plays a decisive role in the development of a company with a competitive edge. A descriptive approach and a quantitative method are the research methodologies employed. All banks owned by the Indonesian government between 2019 and 2023 made up the study's population. Through assessment, the sample was employed. With a significant value (α) of 0.076 and a t-count value of 1.825, the study's findings were found to be greater than 0.05 (0.076> 0.05). The study's partial results revealed a t-count value of 2.944 and a significance value (α) of 0.006, meaning that 0.006 is less than 0.05.